FAKTORËFAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN IMUNISASI HEPATITIS BË0 PADA IBU YANG MEMILIKI BAYI DI PUSKESMAS BONAI DARUSSALAM PASIR PANGARAIAN KABUPATEN ROKAN HULU - Ardhiyanti, Yulrina (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2016)
Universal Child Immunization (UCI) target of Hepatitis B immunization must be achieved 80 % in national, province, regency or even a village. PD3I surveillance data shows scope of HBË0 (0Ë7 days) immunization in Riau, from 2007-2013 still below national targets. Based on information from paramedic in Bonai Darussalam Health Care, low immunization coverage because some people do not know the benefits and afraid if their infants get immunization an earlier time. This study aims to understand related factors of provision Hepatitis Bâ0 immunization in Bonai Darussalam Health Care, Pasir Pangaraian, Rokan Hulu in 2016. Quantitative research methods and research design used cross sectional. The study was conducted in Bonai Darussalam Health Care, Pasir Pengaraian in February 2016 using questionnaires with 50 people total respondents. Sampling was taken by accidental sampling technique. The results show that 42 people (84%) did not give HB- 0 immunization. Test results chi-square statistic show connection between respondentâs knowledge with HB-0 immunization OR = 2.0 (95% CI 1.22 to 3.26), futhermore, there is a correlation relationship between the respondentâs attitudes with immunization HB-0 OR = 21.8 (95% CI 1.19 to 2.72), and the relationship between the respondents educational with HB-0 immunization OR = 1.8 (95% CI 1.20 to 2.95). A recommendation for paramedic in Bonai Darussalam Health Care is to improve their performance in terms of providing information to mothers who have babies, private midwives and herbalists in the area and it hopes that mother could be motivated to provide immunization HB-0.